THE CONCEPT RESEARCH OF DEVELOPMENT PEDAGOGICAL COMPETENCE OF A FUTURE TEACHER OF PSYCHOLOGY IN MAGISTRACY - Cherepekhina, Olha (Continuing Professional Education: Theory and Practice, 2020)
The article is devoted to presentations the author’s concept research of development pedagogical competence of a future teacher of psychology in a magistracy. Author build their own concept of further research based on such scientific-theoretical and methodological foundations such as: axiological; acmeological; activity; competence, professionography; system, personal and human-centered approaches. It is established that the phenomenon of pedagogical competence was studied by scientists from various conceptual approaches, which allowed the author to build his own concept of further research, based on scientific, theoretical and methodological principles.